PENGARUH PENAMBAHAN EKSTRAK DAUN SINGKIL (Premna cordifolia) SEBAGAI ANTIOKSIDAN ALAMI TERHADAP KUALITAS MINYAK KELAPA : The Effect of Addition of Singkil Leaf Extract (Premna cordifolia) as A Natural Antioxidant On The Quality of Coconut Oil (Cocus nucifera) - Dian Fitriarni; Assroruddin; Irfan Cholid; Aris Purnama (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2023)
Coconut oil is one of the top vegetable oil because of cheap in processing and contains various bioactive antioxidants. The shelf life of coconut oil is relatively short, so it is necessary to extend its shelf life by adding antioxidants. Antioxidants as the additional ingredients to prevent increasing the percentage of Free Fatty Acid (FFA) that affect its shelf life. The best source of antioxidants is from plants, such as singkil leaves. In order to know the effect of this leaves extract, this study aims to analyze the effect of singkil leaf extract on the percentage of FFA and peroxide during 28 days. Coconut oil was produced using the heating method, the singkil leaf extract was obtained by the maceration then was added to coconut oil (1%, 3%, and 5%). As the result, more extract was added showing a significant decrease in FFA and peroxide during the 28 days. Adding 5% of the extract was the best that displayed both FFA and peroxide. The lowest FFA value (range 0.05-0.09%) while the peroxide value ranges from 2.6 to 4.2 mg-eq O2/kg-fat. The statistical analysis showed that singkil leaf extract had an effect on the FFA and peroxide of the coconut oil.